The Influence of Empowering Leadership and Certified Teachers on Teachers’ Performance - Eni Masanti; Nila Kesumawati; Andi Rahman (Journal of Social Work and Science Education, 2026)
This study aims to analyze the influence of empowering leadership and teacher certification on teacher performance, both partially and simultaneously, within State Elementary Schools in Suak Tapeh District, Banyuasin Regency. Employing a quantitative expo-facto approach, data were collected via questionnaires and documentation from 83 teachers and analyzed using SPSS. The results indicate that both factors significantly and positively affect performance. Empowering leadership partially enhances teacher performance by fostering autonomy and support. Similarly, teacher certification status independently contributes to improved performance, likely through formal recognition and financial remuneration. Most substantially, the combined effect of empowering leadership and teacher certification exerts the strongest simultaneous influence on overall teacher performance. The novelty of this research lies in its specific examination of this dual-variable model in a rural educational context, highlighting how structural policy (certification) and daily managerial practice (leadership) interact. A key practical implication is the need for integrated school policies that combine certified teacher recruitment with ongoing leadership training for principals to cultivate an empowering work environment. This study contributes to the educational management literature by providing empirical evidence from a district-level setting, underscoring that both systemic incentives and localized leadership are critical levers for enhancing teacher efficacy.